2020
DOI: 10.21203/rs.3.rs-26070/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single-arm feasibility study of community-delivered Baduanjin (Qigong practice of the eight Brocades) training for frail older adults

Abstract: Background: Frailty is a common geriatric syndrome, characterized by reduced physiologic reserve and increased vulnerability to stressors, due to cumulative decline in multiple physiological systems. We studied the feasibility of a community-delivered Baduanjin (BDJ) training program among pre-frail/frail community-dwelling older people. We examined 1) safety (adverse events), physical and psychological effects; and 2) feasibility of recruitment, retention, adherence; recruitment efforts and any program challe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Most of the studies were conducted in China, including ten in Fujian [ 20 29 ], six in Beijing [ 19 , 30 34 ], five in Taiwan [ 35 39 ], five in Guangdong [ 7 , 40 43 ], four in Hong Kong [ 6 , 44 46 ], three in Shanghai [ 18 , 47 , 48 ], two in each of Hebei [ 49 , 50 ], Jiangsu [ 51 , 52 ], Sichuan [ 53 , 54 ], and Hubei [ 17 , 55 ], and one in each of Tianjin [ 4 ], Shanxi [ 56 ], Jiangxi [ 57 ], and Macau [ 58 ]. One study was conducted in Singapore [ 59 ], and one study was conducted in the USA [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies were conducted in China, including ten in Fujian [ 20 29 ], six in Beijing [ 19 , 30 34 ], five in Taiwan [ 35 39 ], five in Guangdong [ 7 , 40 43 ], four in Hong Kong [ 6 , 44 46 ], three in Shanghai [ 18 , 47 , 48 ], two in each of Hebei [ 49 , 50 ], Jiangsu [ 51 , 52 ], Sichuan [ 53 , 54 ], and Hubei [ 17 , 55 ], and one in each of Tianjin [ 4 ], Shanxi [ 56 ], Jiangxi [ 57 ], and Macau [ 58 ]. One study was conducted in Singapore [ 59 ], and one study was conducted in the USA [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven trials included healthy participants only [ 17 , 20 , 22 , 30 , 33 , 36 , 37 , 39 , 49 , 55 , 60 ], and the remaining 36 included participants with a variety of physical and mental health conditions [ 4 , 6 , 7 , 18 , 19 , 21 , 23 29 , 31 , 32 , 34 , 35 , 38 , 40 48 , 50 54 , 56 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies indicate that Baduanjin has positive physiological and psychological effects for older adults with/without chronic disease, for example, improving cognitive function for older adults with or without cognitive impairment [ 20 ], alleviating cancer-related fatigue in cancer patients [ 21 ], and alleviating musculoskeletal pain in older people with chronic low back pain [ 22 ]. A recent preliminary study assessing the feasibility and efficacy of Baduanjin for prefrail/frail community-based older adults found that Baduanjin training was safe and feasible for prefrail/frail older adults with the potential to improve physical and cognitive function, reduce fall risk, improve psychological well-being, and reverse frailty status [ 23 ]. Two other studies also showed that 8-12 weeks of Baduanjin training was effective in improving balance, leg strength and mobility and was a safe and sustainable form of home-based exercise for people with chronic stroke or community-dwelling older adults [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%